C16-Ceramide Analog Combined with Pc 4 Photodynamic Therapy Evokes Enhanced Total Ceramide Accumulation, Promotion of DEVDase Activation in the Absence of Apoptosis, and Augmented Overall Cell Killing. (7th October 2010) - Separovic, Duska; Saad, Ziad H.; Edwin, Ethan A.; Bielawski, Jacek; Pierce, Jason S.; Buren, Eric Van; Bielawska, Alicja
Abstract : Because of the failure of single modality approaches, combination therapy for cancer treatment is a promising alternative. Sphingolipid analogs, with or without anticancer drugs, can improve tumor response. C16-pyridinium ceramide analog LCL30, was used in combination with photodynamic therapy (PDT), an anticancer treatment modality, to test the hypothesis that the combined treatment will trigger changes in the sphingolipid profile and promote cell death. Using SCCVII mouse squamous carcinoma cells, and the silicone phthalocyanine Pc 4 for PDT, we showed that combining PDT with LCL30 (PDT/LCL30) was more effective than individual treatments in raising global ceramide levels, as well as in reducing dihydrosphingosine levels. Unlike LCL30, PDT, alone or combined, increased total dihydroceramide levels. Sphingosine levels were unaffected by LCL30, but were abolished after PDT or the combination. LCL30-triggered rise in sphingosine-1-phosphate was reversed post-PDT or the combination. DEVDase activation was evoked after PDT or LCL30, and was promoted post- PDT/LCL30. Neither mitochondrial depolarization nor apoptosis were observed after any of the treatments. Notably, treatment with the combination resulted in augmented overall cell killing. Our data demonstrate that treatment with PDT/LCL30 leads to enhanced global ceramide levels and DEVDase activation in the absence of apoptosis, and promotion of total cell killing.